What Everyone Should Say about Symmetries (and How Humeans Get to Say It). Issue 4 (December 2019) - Hicks, Michael Townsen
Abstract : The laws of nature have an internal explanatory structure. This leads to interesting questions for metaphysicians of laws. What is the nature of this explanation? Marc Lange has recently argued in favor of metalaws: higher-order laws governing other laws, of which symmetry principles may be an example. Lange argues that his view, unlike its competitors, can make sense of the explanatory power of symmetries. I agree with Lange about the explanatory structure of laws but disagree with him about the nature of this explanation. I then present a Humean view that neatly captures the explanatory power of symmetry principles.